Efektifitas Perencanaan Pembelajaran dalam Pembelajaran Pendidikan Agama Islam di Sekolah - Isnawardatul Bararah (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2017)
Teaching activities is the process of delivering information and transfer of knowledge from teachers (teachers) to students (students). in it there is a process for students who did not understand to understand, and who do not understand to understand. This achievement will only be achieved if it is based on established learning planning and healthy learning conditions. Learning activities can be implemented well if students and educators alike have the same desire to succeed the learning program. Conditions such as considerations that must be prepared by teachers in order to realize the learning program. These preparations include curriculum, teaching materials, methods and instructional media used, assessment instruments as a means of evaluation.